2011
DOI: 10.1158/1078-0432.ccr-10-1763
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Krestin Is a Novel TLR2 Agonist that Mediates Inhibition of Tumor Growth via Stimulation of CD8 T Cells and NK Cells

Abstract: Purpose: Polysaccharide krestin (PSK) is a mushroom extract that has been long used in Asia and recently in Western countries as a treatment for cancer due to its presumed immune potentiating effects. Although there have been reports of clinical responses after patients have ingested PSK, the mechanism of action of the agent remains undefined. The current study was undertaken to investigate the mechanism of the antitumor actions of PSK.Experimental Design: The immunostimulatory effect of PSK was first evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 47 publications
(53 reference statements)
4
95
0
Order By: Relevance
“…We recently demonstrated that the level of TLR2 expressed on B16F10 melanoma cells determines their invasive activity in response to the endogenous factors released from tumor cells [12] . However, contradictory observations by others indicate that TLR2 activation is able to induce inflammatory cytokines and activate NK cells in vitro and in vivo and protect mice from tumor development and progression [31,32] . In the current study, we find that blocking TLR2 effectively reverses the immunosuppressive characteristics of the microenvironment by suppressing the expression of TGF-β1, IDO, and COX2 and attenuating the infiltration of M2 and Tregs cells.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that the level of TLR2 expressed on B16F10 melanoma cells determines their invasive activity in response to the endogenous factors released from tumor cells [12] . However, contradictory observations by others indicate that TLR2 activation is able to induce inflammatory cytokines and activate NK cells in vitro and in vivo and protect mice from tumor development and progression [31,32] . In the current study, we find that blocking TLR2 effectively reverses the immunosuppressive characteristics of the microenvironment by suppressing the expression of TGF-β1, IDO, and COX2 and attenuating the infiltration of M2 and Tregs cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of specific TLR agonists was assessed using the secretory embryonic alkaline phosphatase (SEAP) reporter gene that is linked to NF-kB activation in response to TLR stimulation. Measurement of SEAP activity using the Quanti-blue substrate (InvivoGen) after TLR agonist treatment was carried out similarly as described previously (24).…”
Section: Nf-kb Activation In Hek Cells Transfected With Tlrsmentioning
confidence: 99%
“…PSK has been reported to activate various immunologically-competent cells 35) -38) . NK cells are also thought to exhibit anti-tumor effects when activated by PSK 36)39) 40) . In this study, the NK cell population was significantly higher in the PSK (+) group compared with the PSK(−) group.…”
Section: Figure─3mentioning
confidence: 99%